Pemasaran Digital dan Penataan Display Produk Pada Ritel Tradisional - Surahman Surahman; Amanda Putri Salsabila; Anggun Regeta Sari; Aquilda Rouw; Dini Amalia; Sofi Nurfadilla; Vina Ulandari (Politeknik Negeri Cilacap, 2024)
Conventional retail store is a retail business that sells convenience products in order to fulfill the people’s daily needs. However, with the presence of various e-commerce platforms, changing consumer behavior, and other technological developments, conventional retail stores need to adapt their business strategy to stay relevant and compete in the digital age by updating its performance digitally. The benefit is to reach wider customers and increase product accessibility. The aim of this survey is to analyze and provide solutions on what kind of strategy that a conventional retail store should do to upgrade its system to a semi-modern or modern retail store. This research uses qualitative methods to understand the phenomena in society related to conventional retail store that are facing the pressure of modernization. The data sources used are primary and secondary data sources. The data contained in this journal is collected by the interview technique to the store owner directly. The results of the research showed specifically the location, Toko Anggun merges into one with the home of the store owner and without a banner or special name board in front of it to introduce the identity or name of the store itself. The method of payment used is still traditional, and does not carry out promotional activities